Experimental observation of negative capacitance in ferroelectrics at room temperature - Appleby,DJR; Ponon,NK; Kwa,KSK; Zou,B; Petrov,PK; Wang,T; Alford,NM; O'Neill,A (Nano Letters: a journal dedicated to nanoscience and nanotechnology, 2014)
Effective negative capacitance has been postulated in ferroelectrics because there is a hysteresis in plots of polarization-electric field. Compelling experimental evidence of effective negative capacitance is presented here at room temperature in engineered devices, where it is stabilized by the presence of a paraelectric material. In future integrated circuits, the incorporation of such negative capacitance into MOSFET gate stacks would reduce the subthreshold slope, enabling low power operation and reduced self-heating.